Assessing the climatic suitability and environmental responses of Anthonomus morticinus Clark (Coleoptera: Curculionidae), a potential biological control agent of Solanum mauritianum Scopoli (Solanaceae) in South Africa - Keizan, Yaron Yakov (University of the Witwatersrand, Johannesburg, 2024)
Insect biology is greatly influenced by the surrounding climate. Desiccation, owing to low relative humidity, poses a significant threat to insect populations, especially those with small body sizes. To avoid exposure to low relative humidity (RH) levels, insects actively seek out nearby microenvironments with raised RH. The flowerbud feeding weevil Anthonomus morticinus is an optimistic agent to limit the spread of the highly invasive Solanum mauritianum throughout South Africa. However, the restricted geographic range shown by A. santacruzi in South Africa due to climatic unsuitability questions how A. morticinus will respond to climatic variables, particularly humidity. The effect of low temperatures has shown to be a limiting factor by Mkhomazi (2022) on the survival of A. morticinus, but the effects of RH remains untested. This study examined the influence of RH on the survival and oviposition of A. morticinus inhabiting S. mauritianum inflorescences. Furthermore, this study also intended to reveal the influence of lethal humidities on A. santacruzi cultures compared to that of A. morticinus when sheltered by host inflorescences. Anthonomus morticinus colonies inhabiting S. mauritianum bouquets were kept at seven relative humidities, from ~80% to ~20% for a period of 14 days. Survival and oviposition, observed by dissection of buds, were recorded. For comparison, colonies of A. morticinus and A. santacruzi were maintained at 20% and 46% relative humidity for seven days to determine if the species had differing responses at the lower RH levels. A. morticinus survival and oviposition showed no significant differences at the decreasing humidity levels. Moreover, no significant differences were observed in the survival between A. morticinus and A. santacruzi at 46% and 20% RH. Weevils residing within the S. mauritianum flowers and shoots were shielded from the unfavourable environmental humidities owing to higher humidity levels within these microclimates. These results highlight the dependence of biological control agents on their hosts for more than just food and reproduction but also for physiological functionality.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Animal, Plant & Environmental Sciences, to the Faculty of Science, School of Animals, Plants and Environmental Science, University of the Witwatersrand, Johannesburg, 2024
Keywords: Biological control; Climatic unsuitability; Floral humidity; Microclimate; Temperature agent selection; Ensemble of small models establishment; Species distribution model; UCTD; SDG-13: Climate action; SDG-15: Life on land